Examining the Volunteering Perspectives of Individuals Participating in Child Welfare Volunteer Activities - Harun Aslan; Tarık Tuncay (İstanbul Üniversitesi Sosyoloji Dergisi)
Acts of volunteerism can be observed in schools, hospitals, and religious institutions, as well as and even more so in nearby streets and apartments. Volunteering behaviors mean different things in different societies based on economic, social, and cultural reasons. While volunteering may sometimes be perceived only as a philanthropic behavior, other times it is considered as the behaviors that contribute to economic development. The opinions of volunteers and administrators working in this field play a significant role in uncovering these meanings. In this context, the study aims to investigate the perceptions that volunteers and managers who participate in Türkiye’s child welfare volunteer activities have toward volunteering based on their experiences volunteering in this field. The field of child welfare is considered a source of intense participation in terms of volunteer work in Türkiye. Therefore, this study has conducted in-depth interviews with 60 volunteers in the field of child welfare. The research has preferred the qualitative research method and phenomenological research design within its scope. The participants’ narratives have been analyzed thematically, with three themes being identified and discussed in detail regarding their perspectives: the personal level, the family and social environment level, and the societal level. These themes reveal the importance of understanding how volunteering is perceived in Türkiye. The research has concluded that individuals’ personal experiences and the perspectives of family, friends, and the society in which one lives are able to affect one’s perceptions about volunteering. Conducting future research on the subject as well as studies on areas where volunteering activities are frequently involved, such as elderly welfare, violence against women and women’s rights, disaster situations, and how to protect the natural environment, may enable a more holistic perspective to be formed in order to reveal how volunteering efforts are perceived in different social services fields.